Aplikasi Arisan Marga Berbasis Web Menggunakan Metode Linear Congruential Generator - Yanto, Rudi; Meiyanti, Ruci (Jurnal Ilmiah FIFO, 2023)
The advancement of technology has significantly impacted various aspects of life, including the traditional practice of "arisan marga" among the Batak ethnic group. Despite having been conducted manually for many years, technological progress has opened up opportunities for automation and efficiency improvement through application development. Therefore, this research aims to develop a web-based application for "arisan marga" that utilizes the Linear Congruential Generator (LCG) method for the drawing of arisan recipients and incorporates e-voting for the election of committee members. The development process involves PHP as the base, supported by the Codeigniter framework and MySQL database. The research results demonstrate the application's effectiveness in managing member data, arisan finances, and conducting fair and random arisan drawings. This innovative solution enables the execution of "arisan marga" in a modern manner, allowing for online implementation while maintaining transparency and fostering close relationships among the members. As an effective alternative, this web application can be utilized by the "marga" community to preserve and modernize the tradition of "arisan" digitally.